2017
DOI: 10.1111/asj.12959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of limit‐feeding diets with different forage‐to‐concentrate ratios on nutrient intake, rumination, ruminal fermentation, digestibility, blood parameters and growth in Holstein heifers

Abstract: The objective of this study was using a wide range of dietary concentrate levels to investigate the major effects of limit-feeding on heifers. Twenty-four Holstein heifers were blocked into six groups and fed with one of four diets containing different levels of concentrate (20%, 40%, 60% and 80% on a dry matter (DM) basis) but with same intakes of metabolizable energy for 28 days. Increasing levels of dietary concentrate caused decreased (P ≤ 0.02) intakes of dry matter (DMI) and neutral detergent fiber and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
6
17
0
Order By: Relevance
“… b SEM, standard error of the mean . c Estimate by DM intake × (1- apparent DM digestibility); the values of DM intake and apparent DM digestibility were shown in our previous study (Zhang et al, 2018 ) . C20, diet contained 20% of concentrate; C40, diet contained 40% of concentrate; C60, diet contained 60% of concentrate; C80, diet contained 80% of concentrate .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“… b SEM, standard error of the mean . c Estimate by DM intake × (1- apparent DM digestibility); the values of DM intake and apparent DM digestibility were shown in our previous study (Zhang et al, 2018 ) . C20, diet contained 20% of concentrate; C40, diet contained 40% of concentrate; C60, diet contained 60% of concentrate; C80, diet contained 80% of concentrate .…”
Section: Resultsmentioning
confidence: 91%
“…Twenty-four half-sib Holstein heifers (8–10 months old and 263 ± 30 kg body weight) with similar initial body condition (2.73 ± 0.03 using a five-point system body condition score) were assigned into one of four F:C treatments: 80:20, 60:40, 40:60, and 20:80, on a dry matter (DM) basis; the groups were named C20, C40, C60, and C80, respectively (Table S1 ). Corn silage was used as the sole forage resource, as reported in our previous study (Zhang et al, 2018 ). Before transfer to treatment diets, all heifers were fed an adaptation diet containing 50% forage and 50% concentrate (DM basis; Table S1 ) for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…In dairy cattle, the lactation phase as well as the genetic factor influence milk production (Santos et al, 2012). In this study with F1 cows in the late lactation, the reduction in milk production is mainly due to the reduction in nutrient, protein, and energy intake required for rumen microbial growth, as verified by Zhang et al (2017). Through compilation, Gabbi et al (2016) found that for Jersey and Holstein cows, 40 and 50% of dietary restriction reduced milk production by 14.2 and 40.9%, respectively.…”
Section: Discussionmentioning
confidence: 59%
“…The confinement of dairy animals has been a tool exploited by farmers, although the cost of feed increases considerably, and it is a major challenge to maintain production and competitiveness in the market. Therefore, Zhang et al (2017) proposed that restriction in diet supply might be an important strategy in the management of confined cattle to reduce feed costs, which may represent more than 60% of the total production cost. However, the restriction in the diet supply can promote rapid mobilization Feed restriction of F1 Holstein × Zebu cows in the final third of lactation modifies intake, nutrient digestibility... Santana et al…”
Section: Introductionmentioning
confidence: 99%
“…In the beef industry, rations are very variable. Some farms are known to feed a ration with a low roughage to feed concentrate ratio in order to maximize energy intake and growth, leading to a delay of ruminal development and fermentation (Zhang et al 2018). In contrast, the veal industry is highly integrated, and the diet is similar for all farms.…”
Section: Introductionmentioning
confidence: 99%